Transformation of Islamic Law: The Case of Malaysia and Qatar In Comparative Context - Azhari, Doni; Asmuni (JURISY: Jurnal Ilmiah Syariah, 2024)
This comparative study investigates the transformations taking place within the Islamic legal framework in Malaysia and Qatar, examining in depth the evolution of the law and the impact of socio-cultural factors. It undertakes a detailed mapping of the complex legal developments in the two countries by analyzing legal codes, delving into historical perspectives, and examining contemporary adaptations. Through this approach, the research reveals how Malaysia and Qatar have reconceptualized their Islamic legal systems. By focusing on similarities, differences and significant transitions in the realm of Islamic law, this study highlights the diverse approaches adopted by the two countries in interpreting and implementing Islamic law, explaining the differences in interpretation and application of the law. The main objective of this study is to provide a comprehensive overview of the evolution of Islamic law in Malaysia and Qatar.